2007
DOI: 10.1007/s10725-007-9170-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ethrel, chlormequat chloride and paclobutrazol on growth and pyrethrins accumulation in Chrysanthemum cinerariaefolium Vis.

Abstract: Pyrethrins and flower yield of pyrethrum (Chrysanthemum cinerariaefolium Viz.) plants were determined after application of ethrel, chlormequat chloride and paclobutrazol. Ethrel at 50, 100, 250 and 500 mg l -l produced a significant positive effect on pyrethrins level, decreased plant height, while 50 and 100 mg l -l significantly increased fresh and dry flower yield. Chlormequat chloride at 1000 and 2000 mg l -l and paclobutrazol (80 and 160 mg l -l ) increased pyrethrins level, single flower weight and decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 22 publications
2
18
0
1
Order By: Relevance
“…No entanto, não é possível afirmar se este é menos eficiente, pois o maior comprimento do colmo pode ter ocorrido em função da dose estudada ou da forma de aplicação (Klein et al, 2002). Além disso, Haque et al (2007) encontrram maior redução da estatura das plantas de crisântemo (Chrysanthemum cinerariaefolium) com o paclobutrazol e não com o clormequat.…”
Section: Resultados Resultados Resultadosunclassified
“…No entanto, não é possível afirmar se este é menos eficiente, pois o maior comprimento do colmo pode ter ocorrido em função da dose estudada ou da forma de aplicação (Klein et al, 2002). Além disso, Haque et al (2007) encontrram maior redução da estatura das plantas de crisântemo (Chrysanthemum cinerariaefolium) com o paclobutrazol e não com o clormequat.…”
Section: Resultados Resultados Resultadosunclassified
“…It was also observed that under ethrel treatment there was a higher incorporation of 14 CO 2 in piretrins. According to the authors this result indicates that ethrel could influence the activity of enzymes linked to the piretrin biosynthetic pathway (Haque et al 2007). In Catharanthus roseus cell suspension, Decendit et al (1993) and Papon et al (2005) observed an increase in geranyl 10-hidroxylase activity when the medium was supplied with cytokinin (zeatin).…”
Section: Oppmentioning
confidence: 98%
“…GA ∅ x Activation of compounds conversion Zhang et al 2005 Catharanthus roseus CYT + x Increase of enzyme activity Decendit et al 1993;Papon et al 2005;Oudin et al 2007 Chrysanthemum cinerariaefolium ET ∅ x Enzyme activation Haque et al 2007 Cymbopogon citratus CYT + ∅ Source of hormone Craveiro et al 1989 C. citratus …”
Section: Artemisia Annuamentioning
confidence: 99%
“…The main purpose of using the growth regulator is to disrupt the biosynthesis of gibberellic acid, thus influencing dry matter production, which is related to the transport of carbohydrates because the development of the cotton plant is related to favorable weather conditions, water and also nutrient availability (ELKOCA; KANTAR, 2006;HAQUE et al, 2007;TAIZ;ZEIGER, 2013). Height control of cotton plant can be efficiently performed with the use of MC, as it inhibits cell growth (LAMAS, 2001).…”
Section: Resultsmentioning
confidence: 99%